Relationship between hemoglobin level and incidence of primary dysmenorrhea among high school students - Gede Reyna Janapriya; Ni Komang Ayu Juni Antari; Nila Wahyuni (Physical Therapy Journal of Indonesia, 2024)
Background: Adolescence is a transitional phase from childhood to adulthood, characterized by significant physical and psychological changes. In women, this phase is characterized by menstruation that occurs regularly. Menstruation is often accompanied by lower abdominal pain known as dysmenorrhea. One of the factors that contribute to the occurrence of dysmenorrhea is the hemoglobin (Hb) level in the blood. Lack of oxygen can affect the pain threshold mechanism, thus increasing the intensity of pain felt during menstruation. This study aimed to identify the relationship between hemoglobin levels and the incidence of primary dysmenorrhea in female students at Public Senior High School 1 Semarapura, Klungkung, Bali. Methods: The research method used a cross-sectional study conducted in the Klungkung area in May 2024. The sample of this study was taken by purposive sampling as many as 103 people, consisting of second-year of senior high school female students aged 16-18 years. The study samples were female adolescents who met certain inclusion and exclusion criteria, including 16-18 years old, already having menstruation, active as a student at Public Senior High School 1 Semarapura, willing to be a research subject and signed informed consent, having moderate to heavy physical activity levels, normal, mild, or moderate stress levels, menarche age ≥ 11 years, menstrual duration not more than 7 days. Exclusion criteria included students with BMI in the underweight or obese category and who were menstruating at the time of the study. Hemoglobin levels were measured using a digital Hb meter, while the incidence of primary dysmenorrhea was measured using the WaLIDD Score. Results: Data analysis using Spearman's rho hypothesis test showed a very strong correlation between hemoglobin levels and the incidence of primary dysmenorrhea with a correlation coefficient (r) of -0.752 and a value of p = 0.000 (p < 0.05). This unidirectional relationship indicates that the lower the hemoglobin level, the higher the intensity of dysmenorrhea pain felt. Conclusion: This study concludes that there is a significant relationship between hemoglobin levels and the incidence of primary dysmenorrhea in female students of a public high school in Bali.